THE DEVELOPMENT OF SUPPORTING TOOL APPLICATION SOFTWARE FOR PROCESSING STATISTICAL DATA BASED ON VISUAL BASIC APPLICATION (VBA) - Mariyana, Rita (Prodi Teknologi Pendidikan, 2015)
Abstract. This study aims to develop to improve the quality of learning by making statistical data processing tools are easy to understand, easy to use by following the flow and statistical methods so that students can quickly perform data processing in both subjects for task completion and the completion of an essay, a thesis or a dissertation. To describe the results of a study to improve the quality of learning with this statistical tool research uses descriptive method, the purposive sampling technique to students taking statistics courses in early childhood teacher education study program Indonesia University of Education. Data from the study, questionnaires, interviews, observation and documentary studies analyzed by quantitative and qualitative techniques. The final product of this study is to improve the quality of products tools of statistical data processing and statistical are quickly understood and easily used not only for Early Childhood Education students but for students taking a statistics course.Keywords : Tools, Learning Media, Process, Statistics Abstrak. Penelitian ini bertujuan melakukan pengembangan untuk meningkatkan mutu pembelajaran dengan membuat alat bantu olahdata Statistik yang mudah dipahami, mudah digunakan dengan mengikuti alur dan metode Statistik sehingga mahasiswa dapat dengan cepat dan mudah dalam melakukan pengolahan data baik itu untuk penyelesaian tugas mata kuliah maupun penyelesaian skripsi, tesis, ataupun disertasi. Untuk mendeskripsikan hasil penelitian dari peningkatan mutu pembelajaran dengan alat bantu Statistik ini penelitian menggunakan metode quasi eksperimen, dengan teknik purposive sampling pada mahasiswa yang mengikuti mata kuliah Statistik pada Program Studi Pendidikan Guru Pendidikan Anak Usia Dini Fakultas Ilmu Pendidikan Universitas Pendidikan Indonesia. Produk akhir penelitian peningkatan mutu pembelajaran ini adalah produk aplikasi alat bantu olahdata Statistik untuk mata kuliah statistik yang cepat dipahami dan mudah digunakan untuk semua mahasiswa yang mengambil mata kuliah Statistik serta untuk pengolahan data penelitian. Kata Kunci : Alat Bantu, Olahdata, Statistik